MAIN PRINCIPLES FOR DETERMINING THE EFFICIENCY OF THE USE OF LAND RESOURCES (Proceedings of International Educators Conference, 2023)
The main principles of effective use of land resources in agriculture, the importance of irrigated land in the intensive development of agriculture are scientifically described in the article.